2015
DOI: 10.1080/09602011.2015.1062115
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and psychological flexibility after a traumatic brain injury and the implications for treatment in acceptance-based therapies: A conceptual review

Abstract: This paper provides a selective review of cognitive and psychological flexibility in the context of treatment for psychological distress after traumatic brain injury, with a focus on acceptance-based therapies. Cognitive flexibility is a component of executive function that is referred to mostly in the context of neuropsychological research and practice. Psychological flexibility, from a clinical psychology perspective, is linked to health and well-being and is an identified treatment outcome for therapies suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 153 publications
2
57
0
Order By: Relevance
“…While it has been found that an ACT approach can be helpful in managing anxiety generally, it is yet to be specifically reviewed for managing anxiety in ABIs (Soo, Tate, & Lane-Brown, 2011). Within the TBI literature, a recent conceptual review has indicated that therapies which promote psychological flexibility (such as ACT) are beneficial to people with TBI who have damage to areas controlling executive functioning (Whiting, Deane, Simpson, McLeod, & Ciarrochi, 2017).…”
Section: Third Wave Therapiesmentioning
confidence: 99%
“…While it has been found that an ACT approach can be helpful in managing anxiety generally, it is yet to be specifically reviewed for managing anxiety in ABIs (Soo, Tate, & Lane-Brown, 2011). Within the TBI literature, a recent conceptual review has indicated that therapies which promote psychological flexibility (such as ACT) are beneficial to people with TBI who have damage to areas controlling executive functioning (Whiting, Deane, Simpson, McLeod, & Ciarrochi, 2017).…”
Section: Third Wave Therapiesmentioning
confidence: 99%
“…Individuals with traumatic brain injury (TBI) often suffer impairments in cognitive flexibility as a result of damage to areas controlling executive processes, such as the PFC (Whiting, Deane, Simpson, McLeod, & Ciarrochi, 2015), resulting in task-switching deficits and excessive perseverance in their behavior. In a recent study, Barbey, Colom, and Grafman (2013) found that cognitive flexibility critically relies on the PFC based on a study of individuals with penetrating (p) TBI.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, caregivers with increased psychological flexibility suffered from less burden, indicating psychological flexibility could be a preventive factor for caregiver burden. In a recent review by Whiting et al, psychological flexibility seems to be associated with positive response to therapies and less self-reported distress in patients with traumatic brain injury [64]. Lamothe et al confirmed in a systematic meta-analysis that MBSR and MBSR-based interventions contribute to professionals' mental health [57].…”
Section: Discussionmentioning
confidence: 99%